Exfoliative Cheilitis in Middle-Aged People - Khaydarova Durdona Munisovna (American Journal of Biomedicine and Pharmacy, 2025)
This article provides an expanded analysis of exfoliative cheilitis in individuals of middle age, focusing on the chronic desquamation of the vermilion, etiological contributors, morphologic deterioration, and therapeutic challenges specific to this age group. The aim is to examine biologic, behavioral, environmental, and microbial influences that disrupt the regenerative balance of lip epithelium and intensify inflammatory reactions. The study also assesses the effectiveness of combined therapeutic approaches directed at restoring barrier integrity, normalizing epithelial turnover, reducing microbial load, and modifying harmful habits. This section provides a detailed and comprehensive overview of exfoliative cheilitis occurring in middle-aged individuals, emphasizing the chronic nature of desquamation, functional impairment, and aesthetic concerns. The discussion focuses on the interplay between intrinsic factors such as reduced mucocutaneous resilience, age-related epithelial turnover decline, hormonal variations, immune modulation, and extrinsic triggers including environmental irritants, occupational exposure, cosmetic use, dehydration, repetitive mechanical trauma, and lifestyle-associated habits. The segment highlights the complexity of diagnosis, noting that persistent crusting and scaling may mask underlying systemic conditions or microbial colonization. The annotation emphasizes the necessity of multidimensional assessment, including clinical examination, microbiological evaluation, and behavioral analysis, to identify all contributing factors. Furthermore, it underscores that effective management requires a strategic combination of topical, systemic, and behavioral interventions aimed at restoring epithelial barrier integrity, reducing inflammatory load, promoting cellular regeneration, and preventing recurrence, thereby improving overall lip function, comfort, and appearance in the affected population.